Perilaku Konsumen Terhadap Pembelian Produk Fashion Di Vilshop Madiun Menurut Perspektif Ekonomi Islam - Friska Ersa Amalia; Luthfi Hadi Aminuddin (Niqosiya: Journal of Economics and Business Research, 2023)
The main objective of this study is to determine the consumer behavior of Vilshop Madiun towards purchasing fashion products according to an Islamic economic perspective, to determine the factors behind Vilshop Madiun consumer behavior in purchasing fashion products and to determine the impact of Vilshop Madiun consumer behavior in purchasing fashion products from an Islamic economic perspective. This research was conducted at Vilshop Madiun. The method used in this research is a qualitative research method. Data and data sources used are primary data and secondary data. The data analysis technique in this study is the deductive thinking method. The results of this study are that there is a gap between theory and practice in the basic norms of consumption behavior, namely the norms of not doing extravagance and simplicity, while the norms that are in accordance with consumer behavior are spending wealth and staying away from miserliness. Factors that influence consumer behavior are reference groups, roles and status, age, economic situation, lifestyle, motivation and attitude. The impact of consumptive behavior is making consumers' finances dwindling, they don't want to save, they are selfish and they regret having lived extravagantly.